A titularidade das indicações geográficas no Brasil. Um estudo comparado a partir das IGs de vinhos finos e espumantes - Colloda, Andresa (My University, 2015)
This dissertation is about Geographical Indications (GIs), a distinctive feature of the Law area known as Intellectual Property, belonging to the field of industrial property, which is, in Brazil, regulated by the Industrial Property Law, number 9279, from May 14, 1996. GIs relate a product or the provision of a service to their place of origin and have strategic importance for those involved, protecting products or services since the development up to the commercialization. GIs have a prominent role in the world, especially in the sector of viticulture, and to the Serra Gaúcha, where are located the first GIs to fine wines and sparkling wines from Brazil, which led, in a decisive way, to the choice of this theme. The aim of this dissertation was to analyze the ownership of GIs in Brazil, comparing the Brazilian legislation with Portugal´s and Argentina´s, in addition to legislation of international organizations. The standardization of the GIs in Brazil began in the nineteenth century, but was in the late twentieth century, in line with the advancement of multilateral agreements, that the current law that regulates the Industrial Property system, and consequently of GIs, was approved. But it was only in 2002 that Brazil had its first national GI, the Indication of Origin of Vale dos Vinhedos. The study showed that both Argentina and Portugal have specific legislation for GIs of wines that covers more aspects and are more specific. The effective application of the GIs in Brazil is recent, and the comparative study showed that Brazilian legislation has gaps and issues not explicitly defined, and in addition, the right to the ownership of GIs is not implemented in the way foreseen by law. A review of the rules governing the Industrial Property system that oportunize and implement the legal support may provide a breakthrough in the protection of regions, products and producers, and can consolidate, increasingly, the Geographical Indications in Brazil.
Esta dissertação tem como tema o instituto das Indicações Geográficas (IGs), signo distintivo da área do Direito denominada Propriedade Intelectual, situada no campo da propriedade industrial que, no Brasil, é regulada pela Lei de propriedade industrial 9.279, de 14 de maio de 1996. As IGs relacionam um produto ou a prestação de um serviço ao seu local de origem e têm importância estratégica para os envolvidos, protegendo produtos ou serviços desde a elaboração até sua comercialização. As IGs possuem papel destacado no mundo, especialmente no setor da vitivinicultura, e na Serra Gaúcha onde estão localizadas as primeiras IG’s para vinhos finos e espumantes do Brasil, o que motivou, de forma decisiva, a escolha desse tema. O objetivo da dissertação foi analisar a titularidade das IGs no Brasil, comparando a legislação brasileira com a de Portugal e da Argentina, além da legislação de organismos internacionais. A normatização das IGs no Brasil iniciou no século XIX, porém, foi no fim do século XX, em consonância com o avanço dos acordos multilaterais, que a atual lei que regula o sistema de Propriedade Industrial e, consequentemente das IGs, foi aprovada. Mas foi somente em 2002, que o Brasil registrou sua primeira IG nacional, a Indicação de Procedência Vale dos Vinhedos. O estudo evidenciou que tanto na Argentina quanto em Portugal existe legislação específica para IGs de vinhos que abarcam mais aspectos e de forma mais precisa. A aplicação afirmativa do instituto das IGs no Brasil é recente e o estudo comparativo evidenciou que a legislação brasileira possui lacunas e aspectos não definidos explicitamente, além do que o direito à titularidade das IGs não é implementado na forma como previsto em lei. Uma revisão das normas que regem o sistema de Propriedade Industrial e que oportunize e implemente o amparo legal pode propiciar um avanço na proteção das regiões, dos produtos e dos produtores e pode consolidar, cada vez mais, o instituto das Indicações Geográficas no Brasil.
Keywords: Indicações geográficas (Marcas de origem) - Brasil; Vinho; Propriedade industrial; Tratados comerciais; Marks of origins - Brasil; Wine; Industrial property; Commercial treaties